2003
DOI: 10.1016/s0911-6044(03)00026-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional MR imaging exposes differential brain responses to syntax and prosody during auditory sentence comprehension

Abstract: In two experiments using event-related functional magnetic resonance imaging we studied healthy adults who listened to sentences that either focused on lexical, syntactic, or prosodic information. In the first experiment two sentence conditions were employed: normal speech which contained function and content words, and pseudo speech which contained function and pseudo words. Sentence processing generally activated the superior temporal region (STR) bilaterally. Relative to normal sentences hearing pseudo sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 98 publications
(123 reference statements)
2
21
0
Order By: Relevance
“…Previous research has implicated the anterior temporal cortex in processing speech containing syntactic structure (Mazoyer et al 1993;Humphries et al 2001Humphries et al , 2005Vandenberge et al 2002;Meyer et al 2003). Similarly, in the present study, we found that bilateral ATL regions demonstrated an increased BOLD response while listening to sentences compared with noun lists.…”
Section: Response Properties Of Anterior Temporal Cortexsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous research has implicated the anterior temporal cortex in processing speech containing syntactic structure (Mazoyer et al 1993;Humphries et al 2001Humphries et al , 2005Vandenberge et al 2002;Meyer et al 2003). Similarly, in the present study, we found that bilateral ATL regions demonstrated an increased BOLD response while listening to sentences compared with noun lists.…”
Section: Response Properties Of Anterior Temporal Cortexsupporting
confidence: 85%
“…Broca's area traditionally has been the central focus in investigating these sentence-level processes (Caramazza and Zurif 1976;Linebarger et al 1983;Caplan et al 2000), but more recent work has suggested that Broca's area plays only a limited role in receptive syntax (Grodzinsky 2000). Thus, investigations of syntactic processing have begun to target other cortical regions, particularly the anterior temporal lobe (ATL) (Mazoyer et al 1993;Dronkers et al 1994Dronkers et al , 2004Stowe et al 1999;Humphries et al 2001Humphries et al , 2005Meyer et al 2003). Some of these studies are reviewed below to summarize the known response properties of the ATL during sentence comprehension.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, an fMRI study investigating neural responses to sentences varying in pitch information (normal intonation versus synthesized flattened speech) and syntactic information (normal speech versus synthesized, de-lexicalized speech) found right fronto-lateral activation in response to prosodic cues. The right-superior temporal region and fronto-opercular cortex were identified as being more involved in processing prosodic information (Meyer et al, 2003). These findings suggest that the right hemisphere frontal lobe support prosodic comprehension.…”
Section: Receptive and Expressive Languagementioning
confidence: 73%
“…Neuroimaging studies of sentence intonation processing have found activation in the frontal operculum extending to the anterior insula (Kotz et al, 2003;Meyer et al, 2003). Magnetoencephalography studies have observed a right-lateralized frontal region to be associated with nonlexical intonation processing (Herrmann et al, 2003).…”
Section: Discussionmentioning
confidence: 99%